Entretien (Criminal justice institutions and the social trajectories of adolescents/youth in Burkina Faso: endogenous/local forms and patterns of punishment, 2022)
This interview focuses on punishment models for adolescents/young people in conflict or at risk with the law, and the conditions for their treatment and social reintegration.
Keywords: Communities; Police; Prisons; Punishment; Children; Juvenile detention; Juvenile delinquency; Disagreement; Legal Committee; Gendarmerie; Local Justice; Deprivation of Liberty; Preliminary Investigation; Investigation Phase; Enforcement of Decisions; Elderly People